The Effect Of Prepregnancy Bmi And Parity On The Duration Of Breastfeeding During Exclusive Breastfeeding - Trias Novita, Regina Vidya; Harnussant , Pratiwi (Al Makki Publisher, 2024)
Obesity Is a condition in a person who experiences overnutrition, Especially Fat Accumulation, Which cause the body to weight more than normal body weight, Indicated with A Body Mass Index (BMI) of more than 29.9 kg/M2 several International Pieces Of Research State That Obese Mothers Fail To Breastfeed Exclusively. Aside From Maternal BMI, Maternal Characteristics Also Support Exclusive Breastfeeding. Maternal Characteristic Factors Include Age, Parity, And Mother’s Education. This Study Aims To Determine The Correlation Between Prepregnancy BMI And Maternal Characteristic Factors With The Duration Of Breastfeeding During Exclusive Breastfeeding. This Research Is Quantitative Research Using A Cross-Sectional Descriptive-Correlational Method With A Retrospective Approach. The Number Of Samples In This Research Was 300 Mothers Who Met The Inclusion Criteria With The Purposive Sampling Technique. Data were collected and processed statistically using the Chi-Square Test and T-test to determine factors related to breastfeeding duration, and the linear regression test with the backward method was used to determine the most influential factors in breastfeeding.The Chi-Square Test Results Showed That All Variables Were Related To The Duration Of Breastfeeding With A P-value <0.05. The Linear Regression Test Showed That The Factors That Had A Significant Effect On The Duration Of Breastfeeding Were Prepregnancy BMI And Parity With A Significance Of 0.00; judging From The Coefficient B Factor Value Of 0.285, Parity Had A More Dominant Effect.